2003
DOI: 10.3732/ajb.90.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Lack of latitudinal trends in wood anatomy of Dodonaea viscosa (Sapindaceae), a species with a worldwide distribution

Abstract: Latitudinal or altitudinal variation in several anatomical characters of wood is common for woody dicotyledonous genera with a wide distribution, but whether such variation exists at the species level is disputed. Latitudinal and altitudinal trends in wood anatomy of Dodonaea viscosa were studied, using 102 samples collected between 41.2° S and 33.3° N latitude and 7-2750 m altitude. We studied variation in four quantitative features: vessel element length, fiber length, vessel frequency, and tangential vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 27 publications
2
34
0
7
Order By: Relevance
“…Several researches have found alterations in the anatomy due to the variation of the geographic position (latitude and longitude) and the altitude for others species. For example, the vP, vD, vF, and MvP parameters of Dodonaea viscosa (Liu and Noshiro 2003), Cornus controversa, C. macrophyla (Noshiro and Baas 2000), some Symplocos family members (van der Oever et al 1981) and Ilex sp (Baas 1973), and a few species of vaccinioideae and vaccinium families (Lens et al 2004) showed a relation with the latitude. These results differed from ours since only vP was statistically significant with the latitude, longitude and altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Several researches have found alterations in the anatomy due to the variation of the geographic position (latitude and longitude) and the altitude for others species. For example, the vP, vD, vF, and MvP parameters of Dodonaea viscosa (Liu and Noshiro 2003), Cornus controversa, C. macrophyla (Noshiro and Baas 2000), some Symplocos family members (van der Oever et al 1981) and Ilex sp (Baas 1973), and a few species of vaccinioideae and vaccinium families (Lens et al 2004) showed a relation with the latitude. These results differed from ours since only vP was statistically significant with the latitude, longitude and altitude.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on the relations of wood anatomy to ecology are reported within species (e.g. Noshiro & Baas 2000;Liu & Noshiro 2003), in genera (e.g. Baas 1973;van den Oever et al 1981;, and within families (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Dickison (2000) e Carlquist (2001) nas dicotiledôneas, caracteres relacionados aos elementos de vaso, como freqüência, comprimento e diâmetro tangencial, são fortemente relacionados às condições ambientais, proporcionando ao mesmo tempo segurança e eficiência no transporte de água e solutos. Liu & Noshiro (2003) destacam a ocorrência de variação intraspecífica na anatomia da madeira em espécies de distribuição restrita (confinadas ao hemisfério Norte ou Sul), enquanto as de ampla distribuição (que ocorrem em todos os continentes, em diferentes condições ambientais) não apresentam. Estes resultados foram observados em Acacia melanoxylon R. Br.…”
Section: Resultsunclassified
“…(Noshiro & Suzuki 1995), Alnus nepalensis D. Don (Noshiro et al 1994), que apresentaram tendências altitudinais e latitudinais significativas e em Dodonaea viscosa Jacq. (Liu & Noshiro 2003), que não apresentou qualquer correlação entre as variações na anatomia do lenho e nas condições ambientais. Liu & Noshiro (2003) especulam que provavelmente algumas espécies são geneticamente variáveis enquanto outras possuem um plano mais rígido na estrutura da madeira.…”
Section: Resultsunclassified
See 1 more Smart Citation